Monitoring the Temperature and Wear of Arduino Uno-Based Lathe Tools Using MLX90614 Sensors in the Turning Process - Febri Firmansyah; Razali (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to design and implement an Arduino Uno-based lathe tool temperature monitoring system using MLX90614 sensors, analyze temperature changes in spindle speed variations, and determine the relationship between temperature and chisel wear. The research was carried out on the ST41 steel turning process using High Speed Steel (HSS) chisels with spindle speed variations of 190 rpm, 300 rpm, and 460 rpm. The temperature of the tool is measured non-contact using a MLX90614 sensor, while the wear of the tool is measured based on the flank wear (VB) value using an optical microscope. The data were analyzed using normality, homogeneity, One Way ANOVA, and Tukey HSD follow-up tests. The results showed that the monitoring system worked well with a sensor accuracy rate of 98.67% and an average error percentage of 1.33%. The variation in spindle speed had a significant effect on the chisel temperature with a significance value of 0.035 (<0.05). The increase in temperature was followed by an increase in chisel wear, with average wear of 0.170 mm at 190 rpm, 0.206 mm at 300 rpm, and 0.277 mm at 460 rpm. The developed system is able to monitor temperature in real-time and can be used as an initial indicator of tool wear conditions in the turning process.